(untitled) (Historia, 2021)
Thomas Victor ("T.V.") Bulpin (1918-1999), the well-known and prolific South African author, wrote nearly thirty books and more than two thousand articles and other publications, mostly on South African hunting, travel and history. Among his well-known “classics” are books, such as Lost Trails on the Lowveld (first published in 1950); The Ivory Trail (1954); Islands in a Forgotten Sea (1959); The Hunter is Death (1962); Natal and the Zulu Country (1966); The Great Trek (1968); Illustrated Guide to Southern Africa (1980) and Tavern of the Seas: The Story of Cape Town, Robben Island and the Cape Peninsula (published posthumously, 2003). Since 2010, several of Bulpin’s well-known books have been republished by Protea Book House in Pretoria – the latest being Storm over the Transvaal (which was first published in 1955 by Howard Timmins in Cape Town).